Measuring Fintech and Digital Banking Scalability to Enhance Financial Inclusion in Indonesia - Pradhipta, Rama Dwika; Wafdayanti, Haasya; Mawardi, Wisnu; Pangestuti, Irene Rini Demi (LifeSciFi, 2025)
This study explores the scalability of fintech and digital banking in Indonesia as a catalyst for financial inclusion, the context centers on Indonesia’s unique challenges, including its archipelagic geography, fragmented regulatory frameworks, and a significant unbanked population (26% of adults), which hinder traditional financial services. The role of this study is to provide evidence-based insights for policymakers, financial institutions, and fintech developers to optimize scalable solutions. By conducting a systematic literature review of peer-reviewed articles, industry reports, and case studies (2015–2025), this research identifies critical drivers and barriers to scalability. Thematic analysis and comparative frameworks were employed to evaluate Indonesia’s progress against global benchmarks. Results reveal that technological infrastructure, regulatory adaptability, and strategic partnerships are pivotal to scalability. However, challenges persist, including low digital literacy and regulatory fragmentation. Data also highlight successful models, such as mobile banking platforms leveraging agent networks to reach remote areas. The article discusses these findings through the lens of collaborative governance, emphasizing the need for multi-stakeholder cooperation. Case studies of Indonesia’s leading fintech firms illustrate how localized innovations such as microloan algorithms and offline transaction modes address inclusion barriers. Key findings suggest that scalable fintech and digital banking can significantly enhance financial inclusion if supported by inclusive policies, infrastructure investment, and public private partnerships. Recommendations include harmonizing regulations, expanding digital education, and incentivizing tech innovation for rural markets. This study contributes actionable strategies to align Indonesia’s digital finance growth with sustainable development goal.